Description of Bradinopyga konkanensis sp. nov. (Odonata: Anisoptera: Libellulidae) from the coastal region of Maharashtra, India - Joshi, Shantanu; Sawant, Dattaprasad (Zootaxa, 2020)
Bradinopyga konkanensis sp. nov. is described based on three males and one female collected from the coastal region of Maharashtra, India. Important characters are illustrated and compared with morphologically similar species Bradinopyga geminata (Rambur, 1842), Indothemis carnatica (Fabricius, 1798), and Indothemis limbata sita Campion, 1923. Bradinopyga konkanensis sp. nov. is so far the only Western Ghats endemic Odonata species associated with lateritic coastal habitats.